The forgotten regional modernism of the military educational-type architecture of the first half of the 20th century: A case of the Pilot School in Pančevo - Rašković, Ivan; Vujović, Jasmina; Brankov, Borjan (Arhitektura i urbanizam, 2025)
Military facilities have traditionally been not only structures of strategic importance, but also symbols of innovation in construction and architectural expression. Once reflecting the modernity and stability of the military as an institution, many of these buildings are now abandoned or repurposed for civilian use – often without clearly defined new functions. Additionally, their urban, architectural, and socio-cultural qualities remain under-researched. This paper focuses on the historical and architectural analysis of the former Pilot School building in Pančevo, the first aviation academy in the Kingdom of Yugoslavia during the interwar period. After serving various military functions – including intelligence training in the 1950s – the building was transferred to civilian use in the 1960s and became makeshift housing for multiple families in the 1990s. Despite its historical and architectural significance, the building lacks proper documentation and institutional support for its restoration. In 2021, the site was placed under preliminary protection. In 2023, on the occasion of the 100th anniversary of the first night flight over Pančevo, a new initiative emerged advocating for the building’s restoration. This research, employing historical interpretation and case study methodology, highlights architecturally valuable features that support its designation as a cultural monument. The paper concludes that the building has strong potential for formal protection and reuse, particularly for cultural or public purposes. Such transformation would preserve this unique example of modernist military architecture and honor Pančevo’s important role in early Yugoslav aviation history.